Integrating Artificial Intelligence Technologies into the Teaching of Islamic Studies at the Intermediate Level in Saudi Arabia: Teachers' Perceptions - Al Saad, Lulwa S. A.; Albahiri, Mohammed H.; Alhaj, Ali Albashir Mohammed (QiST: Journal of Quran and Tafseer Studies, 2026)
This study explored Saudi intermediate-level Islamic Studies teachers' views on integrating artificial intelligence (AI), the conditions needed for its effective use, and the challenges surrounding its adoption. A questionnaire was distributed to 151 teachers and analyzed using descriptive statistical methods, including frequencies, percentages, means, standard deviations, and relative weights, guided by a five-point Likert scale. The findings reveal strong support for AI as a supportive instructional tool that enhances lesson planning, simplifies complex concepts, encourages active learning, and enables personalized instruction. Teachers also expressed high awareness of ethical responsibilities, particularly regarding the verification of AI-generated content, protection of students' data privacy, prevention of plagiarism, and the need for responsible teacher supervision. In terms of adoption criteria, participants emphasized the importance of maintaining doctrinal accuracy, preserving the authenticity of Islamic knowledge, fostering critical and reflective thinking, and facilitating the transfer of learning to real-life contexts. They further highlighted essential technical and governance requirements, such as secure access control, data confidentiality, accurate Arabic-language support, fairness, and clear ethical guidelines. Teachers showed a clear preference for specialized AI applications designed for Islamic Studies and immersive technologies such as virtual and augmented reality, while expressing less confidence in data mining and big data tools. Reported challenges were largely systemic, including limited infrastructure, insufficient professional training, and the absence of clear institutional policies. Overall, the study underscores that successful AI integration in Islamic Studies requires coherent alignment between pedagogy, technology, and ethics, supported by robust governance frameworks and continuous professional development.